Effect of Foliar Spray of Boron and Plant Growth Regulators on Hybrid Seed Yield and Quality of Ridge gourd - MANJULA,; SR DODDAGOUDAR,; SN VASUDEVAN,; NM SHAKUNTALA,; AR KURUBAR, (Seed Research, 2026)
An experiment was carried out in a randomized block design with three replications to study the effect of boron and plant growth regulators on hybrid seed yield and quality of ridge gourd. The experiment consisted of seven treatments viz., T1: control, T2: boron (1 g/l), T3: boron (1 g/l) + GA3 (50 ppm), T4: boron (1 g/l) + NAA (0.3 ml/l), T5: boron (1 g/l) + triacontanol (1.5 ml/l), T6: boron (1g/l) + homobrassinolide (0.5 ml/l) and T7: boron (1 g/l) + humic acid (2 ml/l). The sprays were given at two to three leaves, peak flowering and fruit initiation stages. Among the various treatments imposed, T3: boron (1g/l) + GA3 (50 ppm) recorded significantly higher vine length (422.0 cm), number of fruits per plant (5.83), fruit length (26.9 cm), fruit diameter (15.5 cm), fruit weight (27.8 g), number of seeds per fruit (46.7), seed weight per fruit (5.4 g), 100 seed weight (11.60 g), hybrid seed yield (31.5 g/plant), (294.6 kg/ ha), seed germination (88.0 %), dehydrogenase enzyme activity (1.293 OD value), shoot length (27.5 cm), root length (15.1 cm), seedling dry weight (942 mg) and seedling vigour index (3749) compared to control (380.0 cm, 5.20, 25.0 cm, 14.0 cm, 23.7 g, 45.5, 4.9 g, 10.80 g, 25.6 g, 239.6 kg, 79 %, 0.096, 23.5 cm, 12.7 cm, 675 mg, 2860.0 and), respectively. Hence, it is concluded that foliar spray of boron (1g/l) + GA3 (50 ppm) once at two to three true leaves, peak flowering and fruit initiation stage improved the seed yield and quality of ridge gourd.